Women's Organization for National Prohibition Reform records - Women's Organization for National Prohibition Reform
Chiefly reponses to a query sent to consuls general and other representatives of foreign countries about their country's liquor policies and regulations. Responses addressed to Mrs. Edward Wales Root, director of research of the Women's Organization for National Prohibition Reform (WONPR).
Organization advocating the repeal of the 18th Amendment to the U.S. Constitution because of concerns about the ineffective enforcement of Prohibition and the lawlessness and disrespect for authority associated with the failure of government-imposed abstinence. Founded in 1929.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States; Liquor laws -- United States; Prohibition; Prohibition -- United States